2020
DOI: 10.1186/s12991-020-00285-4
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of mood disorders among educationally active older adults in Bialystok, Poland: a cross-sectional study

Abstract: Background: Mood disorders in older people are an increasingly serious health and social problem, and their prevalence increases with age. The most common mood disorders are bipolar disorder, which is the occurrence of mania and hypomania, and depressive disorders. The aim of this study was to determine the prevalence of mood disorders in a group of educationally active elderly people living in Bialystok, Poland. Methods: The study included a total of 162 people-residents of Bialystok-aged 60 or older; 135 wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 82 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…Previous findings also reported a positive association of high education level with anxiety and depression 24 . A cross-sectional study from Poland, using the 30-item GDS, reported depression as a significant social and health problem among educationally active elderly 25 . Health knowledge and health perception influenced by the education level can affect healthcare-seeking behaviours among Myanmar elderly 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings also reported a positive association of high education level with anxiety and depression 24 . A cross-sectional study from Poland, using the 30-item GDS, reported depression as a significant social and health problem among educationally active elderly 25 . Health knowledge and health perception influenced by the education level can affect healthcare-seeking behaviours among Myanmar elderly 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Regular physical activities can improve the depression symptoms of the elderly, and physical activities of different intensities have certain effects on improving the depression symptoms of the elderly. [ 19 21 ] A study suggests that sedentary behavior for a long time will increase the risk of depression in the elderly. Regular physical exercise can reduce the risk of depression in the elderly, and the risk of depression in the elderly who lack physical exercise is higher than that in the elderly who regularly exercise.…”
Section: Methodsmentioning
confidence: 99%